Control of Vehicle Ownership and Market Competition: Theory and Singapore's Experience with the Vehicle Quota System - Koh, Winston T. H. (Institutional Knowledge at Singapore Management University, 2003)
This paper studies the impact of vehicle quota system on the market structure of Singapore's car distributorship industry. Using recently available data, we analyzed the populations and new registrations of different brands of passenger car and motorcycle. We found an increase in market concentration in the car distributorship industry, as the market shares of the top distributors have increased steadily, even though the annual growth rate of vehicle population is capped at 3% per annum. We also found that average dealership markups for passenger cars for the period August-September 2002 are similar to those reported in earlier studies. We relate these empirical findings to a theoretical model of a differentiated-good oligopoly operating under an industry sales constraint.